A Dyadic Perspective on Engagement in Advance Care Planning. Issue 1 (2nd December 2016) - Fried, Terri; Zenoni, Maria; Iannone, Lynne
Abstract : Objectives: To understand the perspectives of both patients and the person who would make medical decisions for them if they were unable (surrogates) on their participation in advance care planning (ACP). Design: Qualitative cross‐sectional study. Setting: Community. Participants: Thirty‐one veterans age 55 years and older and their surrogates. Measurements: In interviews conducted with both the veteran and surrogate, they were asked to discuss their participation in four ACP activities: communication about life‐sustaining treatment, communication about views on quality of life, completion of a living will, and appointment of a healthcare proxy. They were asked about barriers to and facilitators of ACP engagement. When they did not agree about engagement, they each provided their perspective on what they believed had or had not occurred. Results: Many of the same barriers to and facilitators of engagement were discussed by both patients and surrogates. These included difficulty thinking about dying, differences in values, and experiences with others that demonstrated the ability of ACP to decrease burden or avoid conflict. Reasons for disagreements in perceptions about whether communication had occurred included surrogates' need for more detailed information, surrogates' lack of readiness to hear what the patient was saying, and surrogates' reliance on what they know about the patient. For some dyads, participation in the study prompted additional communication, resulting in a better shared understanding of ACP engagement. Conclusion: Surrogates can both impede and facilitate engagement in ACP, and they can hold different perceptions from patients regarding this engagement. Efforts to promote ACP may be most successful if they assess and address both patients' and surrogates' attitudes and help to facilitate clear communication between them.